Promoting ecosystem-friendly irrigation farm management practices for sustainable livelihoods in Africa: the Ghanaian experience - Caesar Agula; Mamudu Abunga Akudugu; Franklin Nantui Mabe; Saa Dittoh (Agricultural and Food Economics, 2018)
Abstract The contribution of farming to food security, nutrition, employment and poverty alleviation in Africa cannot be overemphasised. This paper analysed the effects of adopting ecosystem-based farm management practices (EBFMPs) on the livelihoods of irrigation farmers in Africa, using Ghana as a case study. The paper employed mixed methods (qualitative and quantitative techniques) for purposes of triangulation and cross validation of the issues. Data were collected using key informant interviews, focus group discussions and administration of a questionnaire to 300 households. A treatment effect model was employed to estimate the effects of adopting EBFMPs on livelihoods of farmers. Specifically, the average treatment effect (ATE) and average treatment effect on the treated (ATET) were estimated and found to be positive and significant. This means that the adoption of EBFMPs has positive and significant implications for farmers’ livelihoods. The paper therefore recommends that irrigation farmers should be educated on the importance of using ecosystem-friendly irrigation practices as this is critical for sustainable livelihood development of the poor and vulnerable, especially irrigators in Ghana who rely on the exigencies of the weather to survive. Irrigation farmers should also be educated on the functioning of irrigation landscape (in terms of water flow from up-stream area to down-stream), and how their activities and practices affect the irrigation water supply system.